Return to play after thigh muscle injury in elite football players: implementation and validation of the Munich muscle injury classification - Ekstrand, J.; Askling, C. l.; Magnusson, H.; Mithoefer, K. (British Journal of Sports Medicine, 2013)
Background: Owing to the complexity and heterogeneity of muscle injuries, a generally accepted classification system is still lacking.